2020
DOI: 10.3390/app10113759
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Taping Effectiveness for the Decreasing Dorsiflexion Range of Motion in Elite Soccer and Basketball Players U18 in a Single Training Session: A Cross-Sectional Pilot Study

Abstract: Ankle sprains have been defined as the most common injury in sports. The aim of the present study was to investigate the ankle taping for the reduction of ankle dorsiflexion range of motion (ROM) and inter-limb in elite soccer and basketball players U18 in a single training session. Methods: A cross-sectional pilot study was performed on 38 male healthy elite athletes divided into two groups: a soccer group and a basketball group. Ankle dorsiflexion ROM and inter-limb asymmetries in a weight-bearing lunge posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Considering this small variability, a specific analysis of the diagnostic accuracy of acute ATFL lesions with varying MRI field strength was not carried out. Furthermore, it is reported that there are no significant differences in the diagnostic performance of MRI using a 3 T magnet rather than a 1.5 T one; significant advantages can only be obtained with a field strength of 7 T, which provides better depiction of ankle anatomy, fluid depositions, and cartilage defects [54][55][56][57]. All the selected studies except for Wei Tan et al described the MRI protocols used, which showed substantial homogeneity: T2-weighted Turbo Spin Echo acquired in the axial plane was employed as the main sequence for a better visualization of the ATFL, using a section thickness of 3-4 mm with an interslice gap of 10%, with the only exception being Verhaven et al, in which a 3D-FSP sequence with a section thickness of 1 mm was employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering this small variability, a specific analysis of the diagnostic accuracy of acute ATFL lesions with varying MRI field strength was not carried out. Furthermore, it is reported that there are no significant differences in the diagnostic performance of MRI using a 3 T magnet rather than a 1.5 T one; significant advantages can only be obtained with a field strength of 7 T, which provides better depiction of ankle anatomy, fluid depositions, and cartilage defects [54][55][56][57]. All the selected studies except for Wei Tan et al described the MRI protocols used, which showed substantial homogeneity: T2-weighted Turbo Spin Echo acquired in the axial plane was employed as the main sequence for a better visualization of the ATFL, using a section thickness of 3-4 mm with an interslice gap of 10%, with the only exception being Verhaven et al, in which a 3D-FSP sequence with a section thickness of 1 mm was employed.…”
Section: Discussionmentioning
confidence: 99%
“…All the selected studies except for Wei Tan et al described the MRI protocols used, which showed substantial homogeneity: T2-weighted Turbo Spin Echo acquired in the axial plane was employed as the main sequence for a better visualization of the ATFL, using a section thickness of 3-4 mm with an interslice gap of 10%, with the only exception being Verhaven et al, in which a 3D-FSP sequence with a section thickness of 1 mm was employed. The oblique coronal-axial plane has already been indicated as the best one for visualizing the ATFL in previous studies [56,57]. None of the selected studies mentioned this scanning plane, but, as stated by Kim et al [20], despite the possibility that the oblique axial-coronal plane could be added to routine MRI scanning protocol for better diagnosis of ATFL injury, the routine axial plane is still adequate and also allows a good evaluation of other ligamentous structures [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…InRomero et al showed similar values in soccer and basketball players with a decrease in ankle ROM and increase in ankle asymmetry in players with prophylactic AT. 38 Despite poor evidence of asymmetrical ROM as a risk factor, foot and ankle biomechanics do not cause disturbances in ROM due to external stimuli, such as AT. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The submission area (v) related to the optimization of sports equipment to increase performance and/or decrease the risk of injury was addressed by three papers. Romero-Morales et al [16] investigated the effectiveness of ankle taping in elite soccer and basketball players and found a decrease in the ROM of ankle dorsiflexion as a reason why taping may be considered a useful prophylactic approach for the prevention of ankle sprain injuries. The study by Wong et al [17] examined the effects of wearing upper-, lower-and full-body compression garments on basketball free-throw shooting accuracy, consistency and the range of motion of body joints.…”
mentioning
confidence: 99%